Percancangan E-Katalog Kopi Khas Bandung Berbasis Website Guna Meningkatkan Kunjungan Wisatawan dan City Branding Kota Bandung Pasca Pandemi - Purbasari, Sophia; Derry Midaya P, G Guci (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
West Java, especially Bandung, as one of coffee-producing regions has its own specialty coffee. The diversity of each type of coffee is an attraction for coffee lovers. Each type of coffee is well-known in various areas in Bandung such as Arjasari Coffee, Burangrang Coffee, Ciwidey Coffee, Gunung Halu Coffee, Gunung Tilu Coffee, Malabar Coffee, Manglayang Coffee, Palasari Coffee, Puntang Coffee and Tangkuban Perahu Coffee. Unfortunately, despite its diversity, there are still many who have not seen Bandung's distinctive coffee, especially for the coffee community and generally for the Bandung community itself. This designs are aims to introduce and provide information about typical Bandung coffee through the media in the form of a website based e-catalog. In the interview data used mixed methods, interviews and questionnaire interviews in Nocturna.id community. The results of this design can be seen that the media used works quite optimally, both in terms of access, distribution and coverage, so that is effective in introducing information about typical Bandung coffee.